Comprehensively Understanding the Role of Anion Vacancies on K‐Ion Storage: A Case Study of Se‐Vacancy‐Engineered VSe2. Issue 15 (4th March 2023) - Sha, Dawei; You, Yurong; Hu, Rongxiang; Cao, Xin; Wei, Yicheng; Zhang, Heng; Pan, Long; Sun, ZhengMing
Abstract: Anion vacancy engineering (AVE) is widely used to improve the Li‐ion and Na‐ion storage of conversion‐type anode materials. However, AVE is still an emerging strategy in K‐ion batteries, which are promising for large‐scale energy storage. In addition, the role of anion vacancies on ion storage is far from clear, despite several proposed explanations. Herein, by employing VSe2 as a model conversion‐type anode material, Se vacancies are intentionally introduced (labeled as P‐VSe2− x ) to investigate their effect on K + storage. The P‐VSe2− x shows excellent cyclability in half cells (143 mA h g −1 at 3.0 A g −1 after 1000 cycles) and high energy density in coin‐type full cells (206.8 Wh kg −1 ). By applying various electrochemical techniques, the effects of Se vacancies on the redox potentials of K‐ion insertion/extraction and the K‐ion diffusion in electrodes upon cycling are uncovered. In addition, the structural evolution of Se vacancies during potassiation/de‐potassiation using various operando and ex characterizations is revealed. Moreover, it is demonstrated that Se vacancies can facilitate the breaking of VSe bonds upon the P‐VSe2− x conversion using theoretical calculations. This work comprehensively explains the role of anion vacancies in ion storage for developing high‐performance conversion‐type anode materials. Abstract : Se‐vacancy‐engineered VSe2 is proposed to reveal the role of anion vacancies on the K + storage of conversion‐type anode materials. The results reveal that Se vacancies boost the first potassiation by offering additional K + adsorption sites and diffusion channels in the intercalation stage and weakening bond strength in the conversion stage. In addition, Se vacancies disappear after the first potassiation.